Modeling and Analysis of Dimensions of Agile Hospital Supply Chain Management with Interpretive-Structural Approach (Case Study: Public Hospitals in Rasht) - Mohammad Reza Mehregan; Shahrokh Yousefzadeh; Ali Reza Hatam Siahkal Mahalle (Tehran University of Medical Sciences, 2021)
Background and Aim: The overall goal of the medical department is to develop and manage an efficient and effective supply chain. Intrinsic instability and unpredictability of treatment needs to require a flexible supply chain. Agility reflects the hospitalchr('39')s response to environmental changes, and agile hospitals are able to provide appropriate services to the patients. Hospital supply chain management agility needs to find the main aspects affecting the relationship and communication between them and to analyze the dimensions together. The purpose of this study was interpretive-structural modeling and analysis of dimensions of agile hospital supply chain management. Materials and Methods: The research design combined descriptive - survey exploratory approach to the future. The population study were doctors, nurses and staff at the University of Medical Sciences. The Delphi technique was used to determine the dimensions of agility and the interpretive-structural modeling approach was used for analysis and modeling. Mick Mac software was used to analyze the dimensions of agility. Results: The final model of agile hospital supply chain management with 16 dimensions had 8 levels, which was at the highest level of cost reduction and at the lowest level of organizational leadership commitment. The results indicate that leadership commitment is the foundation of supply chain agility in the hospital. Knowledge management variable had low impact and effectiveness and was known as a secondary leverage variable. The results showed that most agile supply chain management aspects of the main causes of complex communication and interaction, and the importance of agility in the hospital of the show.  Conclusion: The analysis and interpretation of functional from the aspect of Impact and Influence of agility dimensions in hospital environment Showed that, Dimensions of strategic planning, human resource development and staff skills training, human resource management and employee satisfaction, process management, process integration and organizational transformation, flexibility, organizational communication development and information management integration, service quality management and continuous improvement, acceptance of new technology and new ideas, speed of service, patient  understand and satisfaction, monitor, find best responds demand and market sensitivity in the strategic area are located and They cause model instability and With high impact and high influence, They play an important role in the agility of hospital supply chain management.